Fife Years After Reform: Assessing the Adequacy of the Pension System in Georgia and EU Countries - Jgerenaia, Emzar; Ghaniashvili, Maka (European Scientific Journal, ESJ, 2024)
Due to demographic changes and increasing life expectancy, more people retire than are added to the workforce. This is the main reason why, in recent decades, there has been a wave of pension system reforms with the primary objective of improving their financial sustainability. However, several actions implemented as part of these reforms negatively affect the adequacy of pension systems because they involve a decrease in the replacement rate. Hence, balancing the goals of sustainability and adequacy poses a primary challenge for pension policymakers in the upcoming years. This paper aims to determine pension systems’ adequacy in Georgia and EU countries based on the Open Method of Coordination (OMC) indicators. OMC evaluates pension systems in terms of three main objectives: adequacy, sustainability, and modernization of pensions. Our methodology is based on multivariate statistical analysis and employs synthetic indicators for adequacy objectives for 2010, 2015, 2018, and 2023. The results of our study show an adverse change in pension system adequacy indicators from 2010 to 2023 in most European countries, including Georgia.